2010
DOI: 10.1007/s10620-010-1238-x
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric Resection and Delayed Gastric Liquid Emptying in Rats

Abstract: The gastroduodenal incoordination and abnormal myoelectricity related to impaired contraction in the antrum caused the delayed liquid gastric emptying in pylorectomy rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…surgery normal propagation was usually restored, indicating that conduction pathways had effectively re-established across healing gastric suture lines. 51 It has now been confirmed that this recovery of conduction is due to ICC regeneration and bridging within gastric myenteric layers across healing scar, 20,56 thereby providing an additional layer of resilience to surgical manipulation.…”
Section: Homeostatic Conduction Anisotropymentioning
confidence: 93%
See 1 more Smart Citation
“…surgery normal propagation was usually restored, indicating that conduction pathways had effectively re-established across healing gastric suture lines. 51 It has now been confirmed that this recovery of conduction is due to ICC regeneration and bridging within gastric myenteric layers across healing scar, 20,56 thereby providing an additional layer of resilience to surgical manipulation.…”
Section: Homeostatic Conduction Anisotropymentioning
confidence: 93%
“…A number of animal studies have also identified the GAP including in canines post-Billroth I, 71 canines post-Whipple, 72 and rats post-Billroth I which also demonstrated regeneration of ICC across the anastomotic scar on histology. 56 Other studies utilizing EGG have found that a subset of patients following distal gastrectomy have new bands of high-frequency activity (~7-12 cpm). These studies followed Billroth I, 73 Billroth II, 74 and various other gastric resections.…”
Section: The Pylorus and The Gastrointestinal Aberrant Pathwaymentioning
confidence: 98%